Morning glory syndrome with Moyamoya disease: A rare association with role of imaging - Ponnatapura, Janardhana (Indian Journal of Radiology and Imaging, 2018)
Morning glory disc anomaly (MGDA) is a congenital optic nerve anomaly characterized by a funnel-shaped excavation of the posterior globe that incorporates the optic disc. Most cases are isolated and not associated with systemic anomalies. Systemic anomalies include midline cranial facial defects, hypertelorism, agenesis of the corpus callosum, cleft lip and palate, basal encephalocele, congenital forebrain abnormalities, and renal anomalies. We report a case of 4-year-old male child who presented with reduced visual acuity on left eye with poor fixation. The left eye demonstrated 6-diopter esotropia. Examination of fundus revealed features of MGDA. The child was further subjected to magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) of brain to rule out other associated anomalies. It demonstrated narrowing at the distal part of internal carotid artery on both sides, left more than right with prominence of lenticulostriate and leptomeningeal vessels. MRI also revealed funnel-shaped excavation of the posterior globe on the left side consistent with MGDA. Ascertaining the accurate diagnosis of MGDA guides appropriate ophthalmic management and should also prompt a search for associated intracranial abnormalities. Although the diagnosis of MGDA is typically made clinically, imaging may feed supplementary value in establishing the diagnosis and reveal the extent and character of associated ocular abnormalities, and cross-sectional imaging permits for evaluation of the globe in the setting of associated opacities of the refractive media, including persistent hyperplastic primary vitreous, which may alleviate the capacity to make this diagnosis on the basis of the fundoscopy examination alone.
Keywords: Magnetic resonance angiography; magnetic resonance imaging; morning glory disc anomaly; Moyamoya disease